PEMBERDAYAAN MASYARAKAT KAMPUNG JURANG BLIMBINGSEBAGAI KAMPUNG SENI DAN BUDAYA DI KOTA SEMARANG MELALUI PELESTARIAN SENI TRADISIONAL UNTUK MENUNJANG KESEJAHTERAAN RAKYAT BERDASARKAN UNDANG UNDANG NOMOR 5 TAHUN 2017 TENTANG PEMAJUAN KEBUDAYAAN - Ana Irhandayaningsih, Triyono Muhyidin (Diponegoro Private Law Review, 2018)
The Blimbing Bluff of Kelurahan Tembalang, Tembalang Sub-district, Semarang City is a Thematic village that was pioneered and projected as one of Thematic Thematic Village of Art and Culture in Semarang City, Central Java. Various types of art are still alive and growing in it. Type of Art Kehoprak, Horse Lumping and Calligraphy are the types of art that live, popular and still cultivated by a group of people in the village. These arts groups are still alive and have the potential to be further enhanced to be more acceptable and favored by today's young generation, and to be competitive with other arts and cultures in Central Java. The problem is how to create traditional arts in the village of Blessing Blimbing which has been abandoned by the young generation is again becoming a popular art by the younger generation and all levels of society, to then be used as a means to communicate various information including law, and the creation of art and culture village become a destination to enjoy artistic tourism, so that in turn the surrounding community can enjoy the positive impact that can improve the populist economy for the achievement of people's welfare. As stipulated in Article 4 and Article 32 paragraph (2) of Law No. 5 of 2017 on the Promotion of Culture, that the purpose and benefits of the promotion of culture among others is to improve the welfare of the people, and strengthen the identity of the nation. Keywords : Social empowerment, Thematic Village